Nuclear Entry of the Circadian Regulator mPER1 Is Controlled by Mammalian Casein Kinase I ɛ - Vielhaber, Erica (American Society for Microbiology, 2000)
The molecular oscillator that keeps circadian time is generated by a negative feedback loop. Nuclear entry of circadian regulatory proteins that inhibit transcription from E-box-containing promoters appears to be a critical component of this loop in both Drosophila and mammals. The Drosophila double-time gene product, a casein kinase I ɛ (CKIɛ) homolog, has been reported to interact with dPER and regulate circadian cycle length. We find that mammalian CKIɛ binds to and phosphorylates the murine circadian regulator mPER1. Unlike both dPER and mPER2, mPER1 expressed alone in HEK 293 cells is predominantly a nuclear protein. Two distinct mechanisms appear to retard mPER1 nuclear entry. First, coexpression of mPER2 leads to mPER1-mPER2 heterodimer formation and cytoplasmic colocalization. Second, coexpression of CKIɛ leads to masking of the mPER1 nuclear localization signal and phosphorylation-dependent cytoplasmic retention of both proteins. CKIɛ may regulate mammalian circadian rhythm by controlling the rate at which mPER1 enters the nucleus.